Pelatihan Tahsin untuk Meningkatkan Kemampuan Membaca Al-Qur’an di SMP N 225 Jakarta - Mufidah, Vika Nurul; Wahyuni, Sri; Ramdhan, Faizal Aji (Universitas Pahlawan Tuanku Tambusai, 2025)
The ability to read the Qur'an properly and correctly is an important basic skill in Islamic education. However, many junior high school students still have difficulty reading the Qur'an according to the rules of tajwid. This community service activity aims to improve the ability of students at SMPN 225 Jakarta to read the Qur'an through tahsin training. The methods used include lectures, demonstrations, hands-on practice, and individual evaluations. The training sessions were conducted over four sessions, covering topics such as the articulation points of letters, tajwid rules, and practice in reading short surahs. Evaluation results showed significant improvements in the pronunciation of Arabic letters, the application of reading rules, and fluency in reading. Additionally, the students demonstrated higher interest and motivation in studying the Quran. Thus, this tahsin training is effective as an effort to improve Quran literacy among secondary school students. It is hoped that this activity will be continued on an ongoing basis by the school.